Kecenderungan Pemilihan Bahasa (Ikhtiar Al-Lughah) Mahasiswa Jurusan Pendidikan Bahasa Arab - Sahrul Muhamad (Naskhi: Jurnal Kajian Pendidikan dan Bahasa Arab, 2023)
This study aims to describe the tendency of choosing the language used by students, especially in the Arabic Education Department. The tendency of choosing the language is seen based on the place and situation where the speech event occurs. This research method uses a descriptive method, a method that seeks to describe a situation or phenomenon that is happening at the present time. The population of this study were students in Arabic education department Tarbiyah and Teacher Training Faculty IAIN Sultan Amai Gorontalo, the number of samples taken was 20 students. The results of this study indicate that on average 60% of those who choose to use Indonesian. In addition to Indonesian, some students also chose to use regional languages as much as 11%, first language 12.5%, mixed languages 13%, and for Arabic as much as 3.5%. The choice of language is influenced by internal and external factors. Internal factors are in the form of different cultural and social backgrounds, while external factor is environment. So, it can be concluded that the tendency of choosing the language of students in Arabic language education is Indonesian in both formal and informal situations. The data obtained in this study describes the results of the use of language variations in the Arabic Education Department so that further research is needed on the influence of cultural and environmental backgrounds on students' language skills.